A qualitative analysis of perceptions and barriers to therapeutic lifestyle changes among homeless hypertensive patients - Moczygemba, Leticia R. (2012)
BACKGROUND: Homeless individuals have higher rates of hypertension when compared to the general population. Therapeutic lifestyle changes (TLCs) have the potential to decrease the morbidity and mortality associated with hypertension, yet TLCs can be difficult for homeless persons to implement due to competing priorities. OBJECTIVES: To identify: 1) Patients' knowledge and perceptions of hypertension and TLCs; and 2) Barriers to implementation of TLCs. METHODS: This qualitative study was conducted with patients from an urban healthcare clinic within a homeless center. Patients ≥ 18 years old with a diagnosis of hypertension were eligible. Three focus groups were conducted at which time saturation was deemed to have been reached. Focus group sessions were audio recorded and transcribed for data analysis. A systematic, inductive analysis was conducted to identify emerging themes. RESULTS: A total of 14 individuals participated in one of three focus groups. The majority were female (n = 8) and African-American (n = 13). Most participants were housed in a shelter (n=8). Others were staying with family or friends (n=3), living on the street (n=2), or had transitioned to housing (n=1). Participants had a mixed understanding of hypertension and how TLCs impacted hypertension. They were most familiar with dietary and smoking recommendations and less familiar with exercise, alcohol, and caffeine TLCs. Participants viewed TLCs as being restrictive, particularly with regards to diet. Family and friends were viewed as helpful in encouraging some lifestyle changes such as healthy eating, but less helpful in having a positive influence on quitting smoking. Participants indicated that they often have difficulty implementing lifestyle changes because of limited meal choices, poor access to exercise equipment, and being uninformed about recommendations. CONCLUSIONS: Despite the benefits of TLCs, homeless individuals experience unique challenges to implementing TLCs. Future research should focus on developing and testing interventions that facilitate TLCs among homeless persons. The findings from this study should assist healthcare practitioners, including pharmacists, with providing appropriate and effective education.